'Wogball', or the World Game? Race and Soccer in Australian Journalism. (June 2016) - Bahfen, Nasya
This article applies theories of news values and print nationalism to the media coverage of the takeover by a foreign consortium based in the Middle East of a Melbourne-based national league football (soccer) club in Australia. In the Australian media, football (soccer) competes for attention with more established or dominant codes such as Aussie Rules and rugby league. Where coverage is accorded to football, it is underpinned by negative contexts. In addition to associating football with violence and hooliganism, Australian sports journalism's overriding theme when it comes to football is to portray the code as foreign, a sport followed by migrants, and a code mired in cultural division. This is despite attempts by the sports' administrators to nationalize the sport and move it away from the ethnic origins of several community and state level clubs—efforts that have been criticized as 'whitewashing' the Australian grassroots of the world game. News values as described by Galtung and Ruge (1965) and nationalism through an imagined community as espoused by Anderson (1991) are mainstays of journalism and media curriculum. This article examines how race, nation and ethnicity are present, reinforced and contested in the discourse of football (soccer), as engaged in by Australian journalism.